Improving the photovoltaic parameters in Quantum dot sensitized solar cells through employment of chemically deposited compact titania blocking layer - Prasad, M. B. Rajendra; Kadam, Vishal; Joo, Oh-Shim; Pathan, Habib M. (ELSEVIER SCIENCE SA, 2017)
Incorporation of compact blocking layer at the Transparent Conducting Oxide (TCO)/Electrolyte interface is an effective method to improve the device performance in QDSSC through mitigation of electron re-combinations at this interface. This paper reports the most facile and cost effective method of depositing a rutile titania Compact Layer (CL) over Fluorine doped Tin Oxide (Fro) substrate and its application in titania based CdS QD sensitized solar cells. The deposited compact layers are characterized to study their structural, optical, morphological and electrochemical properties using X-Ray Diffractometry, UV-Visible spectroscopy, Scanning electron microscopy, Cyclic Voltammetry and Contact Angle measurements. Sandwich solar cells are fabricated using these CL based electrodes and characterized using Electrochemical Impedance Spectroscopy, Open Circuit Voltage Decay and J-V characteristics. The CL incorporated CdS QDSSC showed more than 100% increase in the photoconversion efficiency (1.68%) as compared to its bare FTO counterpart (0.73%) proving the efficacy of employed strategy. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: CONDUCTING GLASS SUBSTRATE; BACK-REACTION; TIO2; PERFORMANCE; EFFICIENCY; RECOMBINATION; IMPROVEMENT